Urban ecosystems, cultural identity and urban environmental planning in 1980s Sydney: the making of Bicentennial Park - Evans, Catherine (International Planning History Society Proceedings, 2016)
In the 1980s in Sydney, as elsewhere, a new framing of the city emerged, in which global health and survival was considered to depend on the local intervention in and transformation of degraded urban environments. Underpinning this shift were distinct changes in meaning that Sydney-siders attached to their natural environment, which in turn shaped planning policy and legislation, directions in ecological research, and ultimately urban landscape projects. This paper charts this transition by examining ways in which ecologists, planners and designers constructed and communicated a new ecological understanding of Sydney in the 1980s and early 1990s, and explores Bicentennial Park as an urban landscape project which translated and expressed this new ecological framing of the city. The findings demonstrate that what we take for granted now—that ecology is urban, and that urban ecology offers a pathway to beneficial strategies for adaptation and resilience to environmental change—is a culturally and politically constructed framing of the city which emerged in the late 1970s through the 1980s. Bicentennial Park, now overshadowed by the surrounding Sydney Olympic Parkland is reconsidered for its contribution to ecological conservation as a basis of urban park design in Australia.